Perception of Teacher Educators'on Inclusive Early Childhood Education Curriculum in South East Nigeria - Aliyu, Aliyu Yaya; Ihisota, Josephine Chinyere; Okonkwo, Juliet Amaka (CV Media Inti Teknologi, 2025)
This study examines the perception of teacher educators regarding the implementation of an inclusive early childhood education curriculum in Southeast Nigeria. Employing a descriptive survey design, a purposive sampling technique was used to select 327 teacher educators from two institutions, namely Michael Okpara University of Agriculture, Umudike (MOUAU), and Alvan Ikoku Federal University of Education, Owerri (AIFUE). Data were collected using a validated questionnaire titled